(3cJGH GdRcGIs - (3edG dWas
(3ChdgG (B:s
(3HSe Gddg (B... (3cJGH GdRcGI GdebQhf HcJGH GdUdGI dJYbHgG HgG aj cJGH Gddg SHMGfg aj bhdg (B{ (3CbjehG GdUdGI hBJhG GdRcGI (B} (3hbO LQi OCH GdabgGA gfG HJbOje cdeGJ jQLY aUdgG Edi CeQjf , GdGhd aj HjGf ehVhY GdMce (B...s
(3BNQgG (B:s
... (3cGf Gdecda eJYHOG Hg aj YHGOGJg Hd fjI NUhU GdOGaY hEf cGf EeGeG Chdi HYOe GdGLRGA (B... (3HNUhU GdeGdc Mjf GdOaY Edi GdOGaY eY GfbdGH GdOGYj Edi (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis